2021
DOI: 10.1111/jfpp.15373
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of ginger essential oil in chitosan‐based microparticles with improved biological activity and controlled release properties

Abstract: The objective of the present work was to encapsulate ginger essential oil (GEO) into chitosan‐based microparticles (CMPs) using the ionic gelation method. The fabricated microparticles showed a particle size range of 342–531 nm with a zeta potential of 23.4–45.4 mV. Fourier‐transform infrared (FTIR) analysis confirmed a successful encapsulation without any chemical alteration of GEO. The maximum encapsulation efficiency (31.18 ± 0.94) was obtained for the sample with essential oil to chitosan ratio of 25%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The morphological properties of nanoparticles have a considerable impact on the release profile of encapsulated compounds (Fathi et al., 2021 ). SEM analysis was used to evaluate the microscopical properties of the developed nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The morphological properties of nanoparticles have a considerable impact on the release profile of encapsulated compounds (Fathi et al., 2021 ). SEM analysis was used to evaluate the microscopical properties of the developed nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The release of biologically active compounds from the nanoparticles could be employed by mechanisms such as disintegration, surface erosion, desorption, and diffusion. [35] The rapid release was observed for the first 2 hrs, with a release percentage of 70.1 %. This could be due to the GEO which was released from its molecules that was adsorbed on the surface of the chitosan nanoparticles.…”
Section: Kinetic Releasementioning
confidence: 92%
“…The samples were then rinsed three times with 0.1 M sodium cacodylate at 10-minute intervals before being post-fixed with 1 % osmium tetroxide at 4 °C for two hours. Again, samples were washed three times with 0.1 M sodium cacodylate at 10-minute intervals, and then dehydrated with acetone in ascending order (35,50,75, and 95 %) for 10 minutes and 100 % for 15 minutes. Dehydrated specimens were placed in a specimen basket and dried in the critical dryer for 90 minutes.…”
Section: Morphological Changes Viewed By Scanning Electron Microscopementioning
confidence: 99%
“…49 Ginger oleoresin and essential oils were encapsulated using this technique. 50–53 Fathi et al 50 encapsulated GEO into the matrices of chitosan-based microparticles (CMPs) based on the ionic gelation method. The fabricated microparticles showed a particle size range of 342–531 nm with a zeta potential of 23.4–45.4 mV.…”
Section: Encapsulation Of Ginger Bioactive Compoundsmentioning
confidence: 99%
“…An improvement in encapsulation efficiency (78.11%) was observed for the produced microparticles with a ratio equal to 25% (GEO/CMPs). Fathi et al 50 reported that the thermal stability and antioxidant potential of GEO were improved by encapsulation. The thermal stability and antioxidant potential of GEO were improved by encapsulation.…”
Section: Encapsulation Of Ginger Bioactive Compoundsmentioning
confidence: 99%